Systematic Literature Review: Analisis Manfaat Tanaman Kencur (Kaempferia galanga L.) - Rohama, Rohama; Amalia, Ghina Rezki; Uljanati, Khairi; Ananda, Hesti Aulia; Intan, Intan; Andriani, Ine (VISA: Journal of Vision and Ideas, 2024)
Indonesia is one of the largest spice producing countries in the world, one of which is kencur (Kaempferia galanga L.), which has various health benefits. This research aims to analyze the benefits of the galangal plant. The method used is Systematic Literature Review (SLR) which includes searching, evaluating and synthesizing related literature. Research results show that galangal contains significant chemical content such as essential oils, flavonoids, phenols and curcuminoids, as well as various other active compounds that contribute to its anti-inflammatory, antibacterial and antioxidant properties.